Diritto penale e diversità culturale un approccio filosofico - Stefano, Biancu (2013)
Globalization and its related migratory phenomena lead to encounters of different cultures and civilizations. But, inevitably, they also produce clashes and conflicts. Criminal law is an emblematic locus of the difficulties that result from the assumption of these conflicts at the level of public policies. On this topic, in Europe, the positions of Mireille Delmas-Marty and Otfried Höffe are emblematic and in certain respects opposed. Starting from these two theoretical options, this paper questions the radical nature of the philosophical, ethical, and anthropological challenge that cultural diversity poses for criminal law and consequently engages in the search for possible ways forward.